Your new health service (1946)
1946 1946 1940s 2 pages S.M.A. Leaflet No. 7 YOUR NEW HEALTH SERVICE Mr. Aneurin Bevan's National Health Service Bill provides that for the first time a complete health service will be freely available to everyone. It embodies therefore one of the fundamental principles of socialism — to each according to his needs. The Bill's purpose is to establish a "comprehensive health service designed to secure improvement in the physical and mental health of the people and the prevention, diagnosis, and treatment of illness." Its three main provisions — a comprehensive health service available to all without limitations, a unified hospital service, and the establishment of Health Centres — mark a step forward the importance of which cannot be overestimated. The S.M.A. believes that this Bill, from the point of view of the patient, which must be paramount, will provide a service far in advance of anything yet available in this country and it therefore has our warmest support. From the view-point of the health worker, the Bill for the first time offers him the opportunity of giving of his best under good conditions, and of working in association with other members of the medical team, with all the impetus to professional enthusiasm that this provides. Hospitals and Specialists All hospitals, both voluntary and local authority, will be taken over by the Minister of Health and as a result for the first time the opportunity for a unified hospital and specialist service will be provided. Anyone who studies the hospital surveys published recently will find in them ample justification for this step. Hospitals will be run by Regional Hospital Boards, of which there will be some sixteen to twenty for the whole country. The present local authority boundaries are quite illogical and urgently need reform, but this will take time. Since a Regional Hospital Board may cover the area or part of the area of several Counties or County Boroughs, election of these Boards would be very difficult at present and the Bill therefore proposes that their members shall be nominated by the Minister of Health after consulting local organisations, including the medical profession and the local authorities concerned. Health Centres The Bill provides that "a main feature of the personal practitioner services is to be the development of Health Centres" in every area. This is a very great step forward. Health Centres will provide facilities for general practitioners and chemists, and for many of the special clinics provided by local authorities, such as ante-natal, and infant welfare clinics. A dental service will be provided but owing to the shortage of dentists, priority will be given to expectant mothers and young people. Midwives and Health Visitors will work from Health Centres, and there is to be a home nursing service. Local authorities are given a new power, to make arrangements for the prevention of illness and the after-care of the sick, which can include such things as special foods and extra comforts. The war-time power of the local authorities to provide home helps, not only during child-birth but in a wider range of circumstances, is to be made permanent, so that domestic help may be provided to any household in which it is needed on grounds of health or age. Health Centres will provide facilities for health 126/TG/377/1/1/34